Substance Use among Muslim Students in Aceh, Indonesia - Harahap, Inda Mariana; Perngmark, Pajongsil; Chanchong, Weena (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Background: Illicit substance use is a serious social problem faced by adolescents worldwide, including adolescents in Aceh and has many negative consequences. In addition, illicit substance use does not fit with the values of Islamic teaching, and is strictly prohibited in Islam. Purpose: The aims of this paper are to determine the prevalence of illicit substance use, the stages of substance use, and types of substance used among Muslim students in senior high schools in Aceh, Indonesia. Method: Four hundred and twenty six students who met the inclusion criteria were recruited from four senior high schools in Banda Aceh by using simple random sampling, and of these, 290 returned a completed questionnaire. A self reported questionnaire was used to collect data. Result: The mean age of the subjects was 15.9 years old and the majority of them were female (68.6%). The study found that the prevalence of substance use was 2.4%with a higher number of females than males who had used illicit substances. The common substances that were used by the students were marijuana and dextromethorphon, as well as intentionally inhaled substances. Lastly, out of the students who had used illegal substances the majority was in the regular use stage (1.4%). Conclusion: This study found that substance use among Muslim students in Aceh exists, although prevalence was low. Thus, several preventive programs may be needed in Aceh not only for Muslims students who have used substances but also for students who have not use illegal substances. Keywords: Adolescents, Substance use, Muslim students, Indonesia.